Cultural Differences and Polish-Chinese Business Relations in Practice - Dębczyńska, Anna (Journal of Corporate Responsibility and Leadership, 2018)
The main aim of the article is to define practical recom-mendations for Polish employees and managers facilitating their multicultural cooperation with Chinese partners and contributing to intercultural management in organisations operating abroad. In order to achieve the aim of the paper, the following operational research questions have been formulated: (1) Which cultural factors have an impact on effectiveness and the quality of Pol-ish-Chinese partnership? (2) What are the biggest difficulties for Poles in relations with Chinese partners? (3) Which aspects are the most significant in building and creating relations with Chinese partners? (4) Which guidelines about cooperation with Chinese partners are useful in practice and allow to succeed? Analysis is based on data collected from the qualitative study. Research methods are direct, in-depth structured interviews as well as partly structured observations conducted by the author.